Repeat infection with Chlamydia trachomatis: a prospective cohort study from an STI-clinic in Stockholm - Edgardh, Karin (BioMed Central, 2009)
BACKGROUND: Infection with genital Chlamydia trachomatis (Ct) is the most common notifiable sexually transmitted infection (STI) in Sweden. A mutated Chlamydia, nvCT, has contributed to the increase. The occurrence of repeat infections is not investigated in Sweden. The current paper presents the study protocol for the first Swedish clinical investigation of repeat Chlamydial infection. The concern of the study is whether a Chlamydia infection at inclusion indicates an increased risk for Chlamydia at follow-up after 6–8 months, gender-specific risk factors for and clinical presentation of repeat infections. METHODS AND DESIGN: Sesam City is a drop-in clinic in the city centre of Stockholm. Patients 20 years and older are admitted. During 2007, the clinic had 15 000 visits, 60% made by men. In December 2007, a cohort study began, and data collection was finished in April 2009. A total of 2813 study participants aged 20–39 years were recruited. Data collection included an anonymous self-administered paper-and-pen questionnaire on sexual behaviour, reproductive health and history of Chlamydia, and condom use. Chlamydia tests were performed by self-sampled specimens, analyzed by the ProbeTec (Becton Dickinson) method, Ct-positive specimens also analyzed with a nvCT-specific method. Data from medical records were summarized in clinical report forms. Patients positive for Chlamydia were retested 4 weeks after treatment. Contact tracing covered sexual contacts during the last 12 months. At follow-up 6–8 months after inclusion, Chlamydia tests were performed, and a new questionnaire and CRF completed. DISCUSSION: A STI-clinic-based prospective cohort study allowed us to survey 2813 adult patients. The collected data will provide gender-specific information on the occurrence of and risk for repeat Chlamydia infection, the occurrence of nvCT, and clinical data and information on sexual behaviour and reproductive health, risk-taking and condom use.